2009
DOI: 10.1177/230949900901700315
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing and Plate Osteosynthesis for Fractures of the Distal Metaphyseal Tibia and Fibula

Abstract: Purpose. To assess the results of concurrent intramedullary nailing plus plate osteosynthesis for fractures of the distal tibia and fibula. Methods. 15 men and 10 women (mean age, 35 years) with concurrent fractures of the distal tibia and fibula underwent intramedullary nailing (for the tibia) and plate osteosynthesis (for the fibula). 17 fractures were type A1, 6 type A2, and 2 type A3. Compound type IIIB or more extensive fractures were excluded. Results. The mean follow-up duration was 2 years. The mean ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 65%
“…Egol et al recommended fibular plating whenever nailing is contemplated in distal tibial fractures [23]. Krischan et al reported good results with this treatment, even if a single distal locking screw was used [35]. Ehlinger et al reported that the absence of supplemental fibular fixation was the only statistically identifiable risk factor for malalignment and recommended primary fixation of all distal third fibular fractures [24].…”
Section: Discussionmentioning
confidence: 99%
“…defined rotational malalignment as a difference greater than 15° between normal and injured tibiae, and reported two cases with malrotation after IM nailing of 93 tibial fractures 21. Williams et al .,22 Krishan et al .,23 Freedman and Johnson,24 O’Dwyer et al .,25 Pintore et al .,26 Lambiris et al .,27 and Tu et al 28. also reported similar findings.…”
Section: Discussionmentioning
confidence: 77%
“…Various authors have published on the treatment of the nonarticular metaphyseal tibial fractures with the application of the intramedullary nailing. [5][6][7] However, little evidence exists regarding the management of distal tibia fractures with articular extension of the fracture into the joint with intramedullary nailing. 8,9 The purpose of the current study was to analyze the clinical, functional, and the radiographic results and to determine the impact of these injuries on the ankle joint.…”
Section: Introductionmentioning
confidence: 99%